ASPEK PENENTU NIAT UNTUK MEMBELI PRODUK RAMAH LINGKUNGAN PENGGANTI PLASTIK PADA MILENNIAL DI INDONESIA - Santi Rimadias (Universitas Multimedia Nusantara, 2019)
Abstract—This research aims to analyze the determining aspect of intention to buy environmentally friendly products as a plastic substitute on the milennial generation in Indonesia, such as social influance, enviromental concern, concern for self image, customer attitude and perceived environmental responsibility. The method of data collection used in this research is primary data by spreading the questionnaire to 95 respondents, 20-39 years using multiple regression analysis. Construction is measured using a defined scale. The results showed that the intention to buy environmentally friendly products as a plastic substitute on the milennial generation in Indonesia is influenced by customer attitude and perceived enviromental responsibility. Meanwhile, social influance, enviromental concern and concern for self image does not affect the green product purchase intention.